Myconnection: The endeavour of bonds with nature mycelium material study - Tezycka, Malina (My University, 2022)
The development of agriculture allowed the human population to grow many times larger than thousands of years ago. Nearly all agricultural practices generate waste in large quantities in numerous countries, while the great advantage of its reuse is omitted. Diverse agricultural, cellulose-based waste substrates are being burnt causing a major source of environmental pollution in developing countries. Incorporating the biomimicry’s ideology, where one organism’s waste material becomes another’s raw material, in the building industry partly brings relief to the environment. Moreover, the meeting point of science and design would allow biology to produce building materials. This thesis explores the potential of bio fabrication and the reuse of biowaste as a paradigm shift toward providing a circular economy by designing materials that can be reused, repaired, and remanufactured. The main scope of the research focuses on the compound of agricultural solid-waste substrates and mycelium. Research has shown that mycelium performed the ability to create a self-grown vast network, binding parts of organic substrate allowing us to produce bio-composites for various uses. The thesis involves biologically driven research to explore the qualities delivered by the composites and their application in the design of an outdoor teaching pavilion, as a tool for human and nature coexistence. The circumstances that we experience in the early stages of our life have a great impact on the shape of our personalities. The concept of outdoor learning concentrates on education through practical activities providing long-lasting effects of the skills development essential for modern life, such as communication, innovation, team spirit, autonomy, and creativity. The greatest values that drive the concept of biophilia are impossible to perceive with the bare eye. The project will attempt to discover such conditions through material-driven design.
Keywords: Bio-fabrication; Mycelium; Outdoor school; Material design